Overweight as a Protective Factor in Dementia Incident in Elderly Residents of Kahrizak Charity Foundation Aged 80 and Older - Maryam Ghaderpanahi; Farshad Sharifi; Hossein Fakhrzadeh; Mojde Mirarefin; Zohre Badamchizade; Mahshid Foroughan; Parvaneh Mohammadkhani; Bagher Larijani (University of Social Welfare & Rehabilitation Sciences, 2010)
Objectives: In this study, the relation of late-life body mass index (BMI) and waist circumference with incident dementia risk was investigatedin a group of iranian elderly peopel. Methods & Materials: In cross-sectional present study 107 elderly residents of the Kahrizak Charity Foundation aged 80 and older were participated. Dementia was assessed using Mini-Mental State Examination questionnaire. Body mass index (BMI) was computed by weight (kg)/ height (m2). Results: In a multivariate logistic regression model, late-life overweight was indicated an independent and significant protective factor against developing dementia (Odd Ratio: 0.24, 95% Confidence Interval: 0.06-0.93), also there was no significant association between waistcircumference and risk of dementia incident. Conclusion: Overweight in late-life was shown as a protective factor against incident dementia risk incident.